Photophysics and optical switching in green fluorescent protein mutants - Creemers, T. M. H. (The National Academy of Sciences, 2000)
We demonstrate by using low-temperature high-resolution spectroscopy that red-shifted mutants of green fluorescent protein are photo-interconverted among three conformations and are, therefore, not photostable “one-color” systems as previously believed. From our experiments we have further derived the energy-level schemes governing the interconversion among the three forms. These results have significant implications for the molecular and cell biological applications of the green fluorescent protein family; for example, in fluorescence resonant energy transfer experiments, a change in “color” on irradiation may not necessarily be due to energy transfer but can also arise from a photo-induced conversion between conformers of the excited species.